Methods for the Trace Oxygen Removal from Methane‐Rich Gas Streams. Issue 1 (6th December 2016) - Peppel, Tim; Seeburg, Dominik; Fulda, Gerhard; Kraus, Markus; Trommler, Ulf; Roland, Ulf; Wohlrab, Sebastian
Abstract: Oxygen removal to very low residual contents in methane‐rich gas streams and carbon dioxide as co‐component (simulated biogas) was achieved via three different methods at various temperatures, namely, by reduction with hydrogen admixtures on Pt/ γ ‐Al2 O3 catalysts, by oxygen absorption affinity of YBaCo4 O7+ δ, and by the catalytic reaction with methane on both the materials, respectively. The three methods have characteristic advantages and disadvantages which are discussed in the context of existing methods for gas treatments focused on oxygen removal. Finally, the advantage of dielectric radio‐frequency heating on the powdered functional materials is suggested as alternative to conventional routes. Abstract : Oxygen removal to trace amounts in methane‐rich gas streams containing carbon dioxide as co‐component was achieved by three different processes. Their characteristic advantages and disadvantages are discussed and compared to existing gas treatment methods for oxygen removal. Dielectric radio‐frequency heating on the powdered functional materials is proposed as alternative to conventional routes.